The social and cultural learning experiences of college students who participate in service learning trips - Bienvenu, Beau, author; Kuk, Linda, advisor; Banman, Nancy, committee member; Lynham, Susan, committee member; McKelfresh David, committee member (Colorado State University. Libraries, 2013)
To make a service learning trip an effective learning experience, it is important to determine what, if anything, students are learning as a result of the experience. The purpose of this phenomenological study is to contribute to the understanding of the lived social and cultural learning experiences for college students who participate in service learning trips.The qualitative research method, with its focus on a social phenomenon and the meaning this phenomenon has to the people who participate in it, was used to study the lived experience of undergraduate college students participating in service learning experiences. This study used the phenomenological research methodology, with its focus on describing the essences of the lived experience. The specific research approach was hermeneutical phenomenology because of the interpretative, rather than strictly descriptive, nature of this methodology (van Manen, 1990). In this study, interpretation was used when analyzing the data, using Kolb's Theory of Experiential Learning as the theoretical framework. The primary method of data collection for this research study was through semi-structured interviews with eight participants who had participated in at least one service learning trip. Three major themes were revealed as a result of these interviews: Social Learning Experiences, Cultural Learning Experiences, and Self-Learning. The sub-themes that emerged for Social Learning Experiences were Bonding and Developing Leadership Skills. The sub-themes that emerged for Cultural Learning Experiences were Reintegration Issues, Differences between Participants and Those Served and Overcoming Differences. The sub-themes that emerged for Self-Learning were Changes in Perceptions of Others and Awareness of Privilege.A number of recommendations for practice came out of this study. These recommendations, which could be potentially useful to Student Affairs Personnel interested in implementing service learning trips,included ensuring that there is a formal reflection component in service learning trips, ensuring that service learning trip participants have some kind of responsibility around coming up with solutions to the problem that they are there to solve, ensuring that participants have ample opportunities to work with the other people involved in the project, including students from other schools, and ensuring that participants have the opportunity to interact with the people they are serving.
Keywords: alternative breaks; hermeneutic; intercultural immersion; phenomenology; service learning; student affairs